Exercise Intervention to Reduce Depressive Symptoms in Adults with Intellectual Disabilities. Issue 1 (August 2014) - Carraro, Attilio; Gobbi, Erica
People with intellectual disabilities are often reported as having depressive symptoms. Although the antidepressant effect of exercise has been systematically recognized, research concerning the role of exercise on depressive symptoms in people with intellectual disabilities is still scant. A 12-wk. exercise intervention for depressive symptoms in a group of adults with intellectual disabilities was conducted. Participants were 16 men and 11 women, randomly assigned to an exercise group ( n = 14) or to a control group ( n = 13). The Zung Self-Rating Depression Scale adapted for people with intellectual disabilities was administered at baseline, after 6 wk. and at the end of the intervention. There were statistically significant reductions in scores for the exercise group compared with the control group. Results support the notion that exercise can improve well-being in people with intellectual disabilities.